2021
DOI: 10.3390/cells10112846
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electrical Stimulation Enhances Consistency of Directional Migration of Adipose-Derived Stem Cells

Abstract: Electrical stimulation is a well-known strategy for regulating cell behavior, both in pathological and physiological processes such as wound healing, tissue regeneration, and embryonic development. Electrotaxis is the directional migration of cells toward the cathode or anode when subjected to electrical stimulation. In this study, we investigated the conditions for enhanced directional migration of electrically stimulated adipose-derived stem cells (ADSCs) during prolonged culture, using a customized agar-sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In many studies, ES has been shown to have significant potential as a physical stimulus for activating intracellular signaling pathways involved in cell migration, proliferation, and differentiation. Based on the results presented in Section , it appears that the PEDOT:PSS scaffold composites containing MXene (P1) exhibited greater osteoinductive potential compared to P0, as indicated by gene expression levels. This suggests that the addition of MXene to the scaffold may enhance its ability to promote osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In many studies, ES has been shown to have significant potential as a physical stimulus for activating intracellular signaling pathways involved in cell migration, proliferation, and differentiation. Based on the results presented in Section , it appears that the PEDOT:PSS scaffold composites containing MXene (P1) exhibited greater osteoinductive potential compared to P0, as indicated by gene expression levels. This suggests that the addition of MXene to the scaffold may enhance its ability to promote osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…23.513372 doi: bioRxiv preprint effects of PEF on wound healing 8,15 . This PEF stimulation has been proved to be better than DC-EF in increasing cell migration speed, promoting cell migration persistence 16,17 , and additionally PEF-treated fibroblasts expressed higher levels of type I collagen further benefiting the wound healing 18 . However, hours of exposure in the current stimulation inevitably affects cell viability due to an electrochemical reaction and the Joule heat effect in the medium 19 .…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, a PC, which can be a direct or alternating current, produces a unidirectional or bidirectional current, allowing a dynamic range of electrical frequency, strength, and duration [ 300 , 302 ]. Cellular directional migration during ES stimulation, otherwise known as electrotaxis or galvanotaxis, is influenced by the polarity of the activated intracellular signaling pathways and Golgi apparatus [ 300 , 302 , 303 ]. However, this phenomenon is cell-type dependent, with MSCs and iPSCs directed toward the anode and neural stem cell (NSC) migration toward the cathode [ 302 , 303 , 304 ].…”
Section: Neurotrophic Support In Neuropathy Treatmentmentioning
confidence: 99%